(3PcQ GdeSGaGJ hUhQ GdCbGdjes - (3CMeO Hf Sgd GdHdNj, CHh RjO GdHdNj,J (B322 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfi PcQJ ai cJGHi gPG CbGdje GdGQV Ydi GdeeGdc hbUOJ efgG HdGO GdESdGe HJaUjd eOfgG hJbSe eG jaQO HGdGYeGd GdeLehYI s
(3BNQgG (B:s
(3hjJUdhf HeUQ hGdTGe ef HMQ GdbdRe agPg GdHdOGf GdeYQhaI hbO RGOJ eedcI GdESdGe ajeG ELJeY EdjgG ef CWQGa gPg GdeeGdc s
(3Hg CTcGd edhfg ddCbGdjes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B134s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdLZQGajG h GdHdOGfs